Evaluation of the effect of local anesthesia on emergence agitation in children subsequent to dental procedures with general anesthesia - Naser Kaviani; Masoud Gheisari (Isfahan University of Medical Sciences, 2012)
AbstractIntroduction: Emergence agitation is a common clinical phenomenon in children undergoing general anesthesia. Possible predisposing factors are rapid regaining of consciousness in an unfamiliar environment, the type of general anesthesia technique used, the patient's mood, duration of anesthesia and age. The aim of the present study was to compare the effects of two general anesthetic methods with and without local anesthetics on emergence agitation of children volunteering for general anesthesia in the recovery room. Materials and methods: In this prospective single-blind clinical trial, 60 children under 6, who volunteered for general anesthesia, were randomly divided into two groups. All the subjects were anesthetized using the same protocol. During the dental procedure in the study groups, the teeth involved were anesthetized with one lidocaine+epinephrine cartridge using the infiltration technique. The children's emergence agitation was evaluated and compared between the two groups. Data was analyzed with t-test, ANOVA Mann-Whitney test and Spearman's correlation coefficient (α = 0.05). Results: There were no statistically significant differences in the means of age, in gender and in the number of treatment procedures between the two groups. Emergence agitation scores in the local anesthesia group at 15- and 30-minute intervals were 9.6±3.92 and 8±2.58, respectively, demonstrating a significantly higher rates compared to the other group (p value = 0.013 and p value = 0.014). However, there were no statistically significant differences at 45- and 60-minute intervals between the two groups (p value = 0.872 and p value = 0.048).Conclusion: Based on the results it was concluded injection of a local anesthetic reduces emergence agitation in children undergoing general anesthesia. Therefore, it is recommended to use this technique in children with no contraindications for local anesthetics. Key words: General anesthesia, Local anesthesia, Pediatric dentistry, Recovery room.